Mathematical model of blades bundle with damping connections - Pesek, Ludek; Pust, Ladislav; Tsybulka, Zhan; Bula, Vítězslav (Eastern-European Journal of Enterprise Technologies, 2013)
A very effective way against undesirable vibrations of turbine blades vibrations is introducing additional damping elements into blade shroud For detail discovering of damping processes, the dynamic tests of five blades bundle were prepared in Institute of Thermomechanics ASCR. Before the experimental research, the preliminary solution of mathematical model has been done. System is modelled by a five masses system including viscous-elastic elements made of rubber VITON the dynamic properties of which strongly depend on the temperature and frequency. Presented contribution is oriented on the theoretical solution at 100 oC when the variability of properties must be considered. The response curves of system with frequency variable parameters are presented. Effect of different forms of excitation force vector F = [F01, F02, F03, F04, F05], where Fi(t) = F0icos(ωt), i =1,..5. Amplitudes F0i are selected according to the measurement in laboratory. Comparison with response curves of system with dry friction connections of masses will be mentioned at presentation as well